The Effect of the Drainage Area on Well and Reservoir Performance - Fidya Varayesi; Rian Cahya Rohmana; Rizqiana Mudhoffar; Ilham Nur E.N. Iskandar (Penerbitan Universitas Trisakti, 2021)
Evaluation of the drainage area of a well is an effort to obtain success in planning field development. The size of the drain area not only affects the production rate but will also affect the distribution of pressure and saturation as well as the physical properties of the fluid and reservoir rock. Determination of optimum well spacing is important in field development management. This paper presents observations on the effect of the drain area on the production rate, pressure drop, and recovery factor. Simulation of the well model with a cylindrical drain area is used for various sizes of drainage areas. Based on the analysis in this study, it is concluded that the size of the discharge area affects the production rate, recovery factor, and pressure drop. The decrease in pressure affects the release of dissolved gas as indicated by changes in the gas-oil ratio (GOR) curve and the peak of the GOR.